International Journal of Neuroscience-Based Learning in Schools: A Bibliometric Analysis - Febrialismanto Febrialismanto; Haryanto Haryanto (UM Purwokerto Press, 2023)
Neuroscience-based learning is an approach to learning that is based on knowledge of how the human nervous system functions and processes information. This approach utilizes neuroscience principles to understand how the learning process occurs in the brain and applies that knowledge to help students learn more effectively. This research aims to determine the publication of neuroscience-based learning in schools published in international journals. This research method utilizes a bibliometric approach to analyze international journals retrieved from Scopus. The obtained data is described with several topics that provide the necessary information. The research findings reveal that the publication of articles on neuroscience-based learning in schools is still concentrated in the United States and Europe. The utilization of information from neuroscience-based learning articles is also prominent in the United States and Europe. The authors of neuroscience-based learning articles in schools are predominantly from America and Europe, with fewer authors from Asia, Australia, and Africa publishing articles on neuroscience-based learning. From the research findings, it can be concluded that the publication of neuroscience-based learning articles is still unevenly distributed worldwide. This can be seen as an indication that neuroscience-based learning is not widely utilized globally.